2015
DOI: 10.1007/s10916-015-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Effective Electrocardiogram Steganography Based on Coefficient Alignment

Abstract: This study presents two types of data hiding methods based on coefficient alignment for electrocardiogram (ECG) signals, namely, lossy and reversible ECG steganographys. The lossy method is divided into high-quality and high-capacity ECG steganography, both of which are capable of hiding confidential patient data in ECG signals. The reversible data hiding method can not only hide secret messages but also completely restore the original ECG signal after bit extraction. Simulations confirmed that the perceived q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…However, only a few authors have focused on embedding secret messages in ECG signals or healthcare systems [12][13][14]. Data-hiding methods, i.e., ECG steganography approaches, have been applied to ECG signals for securing patient information [15][16][17][18][19][20][21][22][23][24][25][26][27]. To protect against manipulations, researchers have presented schemes for digital watermarking of ECG signals [28][29][30][31].…”
Section: Overview Of Relevant Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few authors have focused on embedding secret messages in ECG signals or healthcare systems [12][13][14]. Data-hiding methods, i.e., ECG steganography approaches, have been applied to ECG signals for securing patient information [15][16][17][18][19][20][21][22][23][24][25][26][27]. To protect against manipulations, researchers have presented schemes for digital watermarking of ECG signals [28][29][30][31].…”
Section: Overview Of Relevant Workmentioning
confidence: 99%
“…Wang et al [25] proposed two methods to perform ECG reversible data hiding. Based on coefficient alignment [26], two kinds of ECG steganographic methods were proposed. Regardless of the aforementioned steganography techniques, the main goal that each method must achieve high embedding capacity given a fixed distortion constraint between the cover and stego signal while allowing reliable retrieval of steganographed data subject to a fixed distortion between embedded and extracted data.…”
Section: Overview Of Relevant Workmentioning
confidence: 99%
“…Two coefficient-alignment based ECG data hiding mechanism is proposed in [14]. Unlike most of the ECG data hiding mechanisms, in here, the authors have embedded the watermarks directly into the ECG samples in the time domain.…”
Section: A Data Hiding Methods Developed For Ecg Signalsmentioning
confidence: 99%
“…Recently, data hiding has played a crucial role in protecting secret data in multimedia files, such as documents, images, and videos [1][2][3][4][5]. In addition, several researchers have presented data hiding for biomedical signals such as an electrocardiogram (ECG) to secure personal sensitive information, including patients' diagnoses [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Simulations confirmed that the average SNR introduced using the proposed method was approximately 42 dB with the payload of size 15,000 bits and a certain degree of robustness. Yang and Wang [12] employed a smart coefficient alignment technique and designed an effective ECG steganography for hiding patients' information. The technique has two approaches: method A and method B.…”
Section: Introductionmentioning
confidence: 99%